2021
DOI: 10.1039/d1bm00400j
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced efficiency of nonviral direct neuronal reprogramming on topographical patterns

Abstract: Nonviral direct neuronal reprogramming holds significant potential in the fields of tissue engineering and regenerative medicine. However, the issue of low reprogramming efficiency poses a major barrier to its application....

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 111 publications
0
8
0
Order By: Relevance
“…We next investigated biophysical cue-mediated neuronal reprogramming of somatic cells on the CBC array generated by DIL. There has been a surge of interest in the direct neuronal reprogramming of somatic cells (e.g., fibroblasts) for clinical applications (Figure a). , However, the low efficiency of converting somatic cells into mature neurons, which originates from the intrinsic epigenetic barriers, remains a critical hurdle for their applications in disease modeling and tissue engineering. , Although several reported biophysical cues, including substrate nanotopographies, have demonstrated effects on neuronal reprogramming, a more systematic screening of varying ECM structures would be beneficial to advance biomaterial design in neuronal reprogramming. …”
Section: Resultsmentioning
confidence: 99%
“…We next investigated biophysical cue-mediated neuronal reprogramming of somatic cells on the CBC array generated by DIL. There has been a surge of interest in the direct neuronal reprogramming of somatic cells (e.g., fibroblasts) for clinical applications (Figure a). , However, the low efficiency of converting somatic cells into mature neurons, which originates from the intrinsic epigenetic barriers, remains a critical hurdle for their applications in disease modeling and tissue engineering. , Although several reported biophysical cues, including substrate nanotopographies, have demonstrated effects on neuronal reprogramming, a more systematic screening of varying ECM structures would be beneficial to advance biomaterial design in neuronal reprogramming. …”
Section: Resultsmentioning
confidence: 99%
“…Improving the reprogramming efficiency and enhancing the functionality of reprogramed cells have remained two major obstacles for the successful translation of cell therapy using iPSs and direct reprogramed cells, despite the significant progress made on exploiting the usage of the above two reprogramed protocols. The current approaches to improve the reprogramming efficiency have been mainly based on chemical signals such as enzyme inhibitors and small molecules, which play an important role in affecting epigenetics or the regulation of signaling pathways. Besides chemical signals, physical cues like micro/nanotopography have played critical roles in enhancing the reprogramming efficacy. , Compared to micro- and nanostructures and topological morphology, mechanical cues from the substrate with similar stiffness to natural tissue or organ would better mimic the native microenvironment of living organisms, which would give us more critical insights on the cell fate decision process and the role of mechanical signals in the reprogramming process. Moreover, the enhancement of functionality of the reprogramed cells is in particular critical but has been rarely reported.…”
Section: Discussionmentioning
confidence: 99%
“…FACS analysis revealed that the E 40 substrate enhanced the reprogramming process, resulting in a 1.5-fold increase in reprogramming efficiency (Figure 3G). Interestingly, the Runx2 + Dlx5-E 40 group could achieve a reprogramming efficiency of 34 4A) in a bone defect model. The schematic diagram in Figure 4B shows the surgical procedure for repairing osteoarticular defects using gel scaffolds embedding different groups of reprogramed cells and untreated controls.…”
Section: Augmented Proportion Of Transdifferentiatedmentioning
confidence: 99%
“…In a mouse model of cerebral infarction, overexpressed Olig2 and Pax6 reprogrammed glial cells into neurons in situ, as confirmed by the expression of the neuron-specific marker doublecortin and electrophysiological assays [ 115 ]. In another study, exogenous Brn2a, Myt1l, and ASCL1 induced mouse embryonic fibroblasts to differentiate into neurons that expressed microtubulin III (TUJ1) and microtubule-associated protein 2 (MAP2) [ 75 ]. POU5F1, SOX2, KLF4, and MYC can stimulate the development of non-neuronal somatic cells into neurons.…”
Section: Transcription Factors Small Molecules and Mirnas That Induce...mentioning
confidence: 99%